PENERAPAN PROGRAM (CORPORATE SOCIAL RESPONSIBILITY) DALAM PERSPEKTIF ENTERPRISE THEORY DAN PRINSIP HUKUM EKONOMI SYARIAH DI PT. BANK SYARIAH INDONESIA - Ramadhan, Ahmad; Siregar, Ihsan Mulia (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
Corporate Social Responsibility (CSR) refers to all relationships that occur between companies and all stakeholders, including customers, employees, communities, owners, governments, suppliers and even competitors. CSR is a concept in which Bank Syariah Indonesia (BSI) voluntarily contributes something towards a better society and a cleaner environment. This study aims to analyze the Implementation of Corporate Social Responsibility in the Perspective of Sharia Enterprise Theory at Bank Syariah Indonesia KCP. Gunung Tua. This research uses qualitative methods, using primary and secondary data, through documentation techniques and conducting interviews with the parties concerned (informants). This research was conducted by analyzing the suitability of the implementation of Corporate Social Responsibility (CSR) at BSI KCP. Gunung Tua with the perspective of Sharia Enterprise Theory. The results of this study indicate in the implementation of CSR at BSI KCP. Gunung Tua cooperates with the National Amil Zakat Institution Bangun Sejahtera Mitra Umat (LAZNAS BSM). Concept and Implementation of Sharia Enterprise Theory at Bank Syariah Indonesia KCP. Gunung Tua includes; Vertical Accountability, Horizontal Accountability (Direct Stakeholders and Indirect Stakeholders) and Horizontal Accountability (Nature).    Broadly speaking, Corporate Social Responsibility carried out at Bank Syariah Indonesia KCP. Gunung Tua is in accordance with the concept of Shariah Enterprise Theory. According to the view of Sharia Economic Law, CSR is in line with Islamic understanding of how humans should care about society and the environment. According to Islamic economic law, there are several principles that apply in CSR programs, including the principle of permissibility (mabda' al-ibahah), freedom of contract (mabda' hurriyyah atta'aqud), consensual / agreement (mabda' ar- radha 'iyyah), binding promises (mabda' at-tawazun fi al mu'awadhah)